Research on Handan City’s Urban Competitiveness and Industrial Economic Agglomeration Under the “532” Industrial Layout (Journal of Global Humanities and Social Sciences, 2024)
With the continuous development and expansion of the global economy, urban competitiveness has become an important indicator of a city’s overall development potential, affecting its ability to attract talent, investment and enterprises. The purpose of this paper is to examine the urban competitiveness and industrial agglomeration of Handan, China. Handan is characterized by stable economic growth, a well-developed transport infrastructure and a base of higher education institutions, but industrial agglomeration is not as pronounced as might be expected given its size and economic status. Handan needs a mix of traditional manufacturing and services with high-tech or cutting-edge industries and needs to transform itself into a more diversified and technology-driven city.